Frequency of adolescent idiopathic scoliosis among high school students from six Northern Lima schools - Vázquez-Lazarte, Ana Sofía (2020)
Objective: To determine the frequency of adolescent idiopathic scoliosis and its association with factors such as age and sex among high school students from six Northern Lima schools. Materials and methods: An observational, analytical and cross-sectional study was conducted in six schools of the Northern Lima Diocesan Network. It assessed the spine deformity among students from the first to fifth years of high school aged between 11 and 18 years old using the Walter Reed Visual Assessment Scale (WRVAS). The statistical analysis was performed using Stata 15 for Windows and the bivariate analysis was conducted using the chi-square test and Student's t-test. A value of p ≤ 0.05 was considered significant. Results: A total of 191 participants were included in the study: 119 males (62.30 %) and 72 females (37.70 %). The average age was 14.46 ± 1.43 years (range: 12 - 18 years). According to the assessment conducted with the WRVAS, 106 participants (55.50 %) had a negative result, 33 (17.28 %) had a dubious result and 52 (27.23 %) had a positive result. Males accounted for 86.56 % of the positive results and the average age of the participants was 14 years. Conclusions: The frequency of adolescent idiopathic scoliosis was 27.23 % (52 participants) according to the assessment conducted with the screening test. Its association with factors such as the sex showed novel results, and its relationship with the age matched those published in previous studies.